Disability in Different Cultures Reflections on Local Concepts - Holzer, Brigitte; Vreede, Arthur; Weigt, Gabriele (Kultur und soziale Praxis, 1999)
How are disability and rehabilitation conceived of in different cultures? How can these concepts be made accessible? Studies from the fields of sociology, ethnology and educational science address these questions, whilst contributors from rehabilitation projects in development cooperation and from self-help movements highlight culturally different perceptions of disability. A distinctive feature of this reader is the dialogue it creates by bringing together scientific praxis and practical work.